Factors influencing post-traumatic stress disorder among police officers in South Korea - Oh, Hye-Kyung; Jang, Cheol Yeung; Ko, Mi Suk (Frontiers in Public Health, 2022)
Objectives: This study aims to identify critical incident trauma (CIT), social support, resilience, and post-traumatic stress disorder (PTSD) in Korean police officers and to determine factors related to post-traumatic stress disorder to obtain basic data for developing a PTSD intervention. Methods: A mixed method approach was conducted by administering structured questionnaires to Korean police officers and semi-structured interviews to seven Korean police stakeholders. The structured questionnaires elicited information on CIT, social support, resilience, and PTSD. To analyze the questionnaire, data from 189 participants were computed using independent t-tests, Pearson’s correlation coefficients, and multiple linear regression analysis. The interview data, which elicited information on difficulties and coping strategies after CIT, police organizational culture, current status of counseling programs, and suggestions for PTSD interventions, were analyzed using an inductive thematic analysis. Results: Factors that are significantly related to PTSD (28.7% of variance) are very healthy subjective health status (B=-0.44, p=.013), CIT (B=0.18, p=<.001), social support (B=-0.38, p=<.001), and resilience (B=-0.18, p=.044). The stakeholders revealed the following PTSD-related factors: the difficulties and limitations of overcoming traumatic experiences, coping strategies, police counseling program status, and opinions on PTSD-related programs. Conclusion: Perceived health status, CIT, social support, and resilience had a strong relationship with PTSD. Therefore, the success of PTSD interventions for Korean police officers should be considered.